Simultaneous measurement of tadehaginoside and its principal metabolite in rats by HPLC–MS/MS and its application in pharmacokinetics and tissue distribution study. (1st January 2021) - Zhang, Cai-Yun; Lu, Ya-Ting; Tan, Yin-Feng; Liu, Qi-Bing; Dong, Lin; Ma, Ning; Lu, Wei-Ying; Su, Zhi-Heng; Zhang, Xiao-Po
Abstract: Context: Tadehaginoside, an active ingredient isolated from Tadehagi triquetrum (Linn.) Ohashi (Leguminosae), exhibited various biological activities. However, the pharmacokinetics and tissue distribution which affect tadehaginoside's therapeutic actions and application remain elusive. Objective: To clarify the metabolism of tadehaginoside in vivo . Materials and methods: The pharmacokinetics and tissue distribution of tadehaginoside and its metabolite p -hydroxycinnamic acid (HYD) were investigated using LC-MS/MS. Pharmacokinetic parameters were determined in 10 Sprague-Dawley rats divided into two groups, the intravenous group (5 mg/kg) and the oral group (25 mg/kg). For the tissue-distribution study, 20 rats were intravenously given tadehaginoside (5 mg/kg) before the experiment ( n  = 4). Biological samples were collected before drug administration (control group) and after drug administration. Results: The linearity, accuracy, precision, stability, recovery and matrix effect of the method were well-validated and the results satisfied the requirements of biological sample measurement. Treatment with tadehaginoside via intragastric and intravenous administration, the calculated C max in rats was 6.01 ± 2.14 ng/mL and 109.77 ± 4.29 ng/mL, and T max was 0.025 ± 0.08 h and 0.08 h, respectively. The results indicated that the quick absorption of tadehaginoside was observed following intravenous administration, and tadehaginoside in plasma of rats with intragastric administration showed relatively low concentration may be due to the formation of its metabolite. Tissue-distribution study indicated that kidney and spleen were the major distribution organs for tadehaginoside in rats and there was no long-term accumulation in most tissues. Discussion and conclusion: These results could provide clues for exploring the bioactivity of tadehaginoside based on its pharmacokinetic characteristics.